In vitro Drug Metabolism Investigation of 7-Ethoxycoumarin in Human, Monkey, Dog and Rat Hepatocytes by High Resolution LC-MS/MS - Feng, Wan-Yong; Wen, Jenny; Stauber, Kathe (Drug Metabolism Letters, 2018)
Background: Recently, it has been an increasing concern on the bioactivation and adverse reactions associated with consumption of herbal and nature products. 7-Ethoxycoumarin is one of coumarin family compounds, but little information is available regarding its potential reactive metabolites. Method: 7-ethoxylcoumarin was incubated individually with human, monkey, dog and rat hepatocytes for 2 hr, metabolites were detected, identified and characterized using high resolution liquid chromagraphy – tandem mass spectrometry. Results: Twenty-eight metabolites (M1 - M28) were detected and identified. O-deethylation, glucuronidation, sulfation, oxygenation, oxidative ring-opening, hydrogenation, glutathionation, dehydrogenation, cysteination, glucosidation, methylation, and hydrolysis were observed. At least sixteen metabolites not reported previously, were newly identified. M1 (O-deethylation, mono-oxygenation and glucuronidation), M3 (O-deethylation and glucuronidation), M5 (hydrolysis and mono-oxygenation), M14 (O-deethylation), M16 (hydrolysis), M22 (oxidative ring-opening and oxygenation) and M27 (monooxygenation) exhibited high mass spectrometric responses in human hepatocytes. M3, M5, M8, M13 (mono-oxygenation), M14, M16, M18 (O-deethylation and sulfation), M22 and M27 exhibited high mass spectrometric responses in monkey hepatocytes. M14, M16, M18, M20 (glutathionation and dehydrogenation) and M27 exhibited high mass spectrometric responses in dog hepatocytes. M1 (Odeethylation, mono-oxygenation and glucuronidation), M3, M5, M13, M14, M16, M17 (cysteination), M18, M20, and M22 exhibited high mass spectrometric responses in rat hepatocytes. Conclusion: Most of new metabolites via oxidative ring-opening and glutathionation were identified. Species differences in metabolism of 7-ethoxylcoumarin in hepatocytes were observed. The analysis of metabolites suggests that 7-ethoxylcoumarin may undergo 3,4-epoxidation responsible for formation of glutathione and its derived cysteine conjugates, carboxylic acid and its glucuronides, glucosides and sulfate.
Keywords: dogs